Variasi Perempuan dalam Ilustrasi Serat Ambiya - Syahrazad, Hanan; Margana, Sri; Marianto, Martinus Dwi (Institut Seni Indonesia Surakarta, 2023)
This study examines the relationship between Islam and Javanese in the illustration of the Serat Ambiya manuscript in the collection of the Sonobudoyo Museum with collection number L 12 PB A. 180. This manuscript is a pesantrenan category manuscript made in 1844 AD. This research uses a phenomenological approach. The material object of the research is the illustration of the female figure in the manuscript. The research focus focuses on 12 selected illustrations which are felt to represent illustrations of human figures in the manuscript.The results of the study show that the illustration of the human figure in Serat Ambiya shows elements of Islam and Java. This can be seen from the depiction of figure illustrations adapted from wayang characters. The female characters are depicted in kemben, like Javanese wayang, but some of these figures have green faces. The use of green color on the face in the illustration of the green color script reflects the piety of a character, in contrast to the meaning of the green face in wayang. While the position of the protagonist and antagonist is in accordance with the wayang stage, namely the main protagonist is always on the right side of the audience, while the antagonist is on the left side. This causes the human figures in the illustrations of the Serat Ambiya manuscript to contain Islamic and Javanese visual elements.